A novel antisymmetric 16‐element transceiver dipole antenna array for parallel transmit cardiac MRI in pigs at 7 T. (31st March 2022) - Elabyad, Ibrahim A.; Terekhov, Maxim; Lohr, David; Bille, Maya; Hock, Michael; Schreiber, Laura M.
Abstract : To improve parallel transmit (pTx) and receive performance for cardiac MRI (cMRI) in pigs at 7 T, a dedicated transmit/receive (Tx/Rx), 16‐element antisymmetric dipole antenna array, which combines L‐shaped and straight dipoles, was designed, implemented, and evaluated in both cadavers and animals in vivo. Electromagnetic‐field simulations were performed with the new 16‐element dipole antenna array loaded with a pig thorax‐shaped phantom and compared with an eight‐element array of straight dipoles. The new dipole array was interfaced to a 7 T scanner in pTx mode (8Tx/16Rx). Imaging performance of the novel array was validated through MRI measurements in a pig phantom, an 85 kg pig cadaver, and two pigs in vivo (74 and 81 kg). Due to the improved decoupling between interleaved L‐shaped and straight dipole elements, the 16‐element dipole array fits within the same outer dimensions as an eight‐element array of straight dipoles. This provides improvement of both transmit and receive characteristics and additional degrees of freedom for B 1 + shimming. The antisymmetric dipole array demonstrated efficient suppression of destructive interferences in the B 1 + field, with up to 25% improvement in the B 1 + homogeneity achieved using static pTx‐RFPA B 1 + shimming in comparison with the hardware‐adjusted state, which was optimized for single transmit. High‐resolution (0.5 × 0.5 × 4 mm 3 ) anatomical images of the heart after cardiac arrest proved good transmit and receive characteristics of the novel array design. Parallel imaging with an acceleration factor up to R = 6 was possible while maintaining a mean g factor of 1.55 within the pig heart. CINE images acquired in vivo in two pigs demonstrated SNR and parallel imaging capabilities similar to those of a reference 8Tx/16Rx dedicated loop array for cMRI in pigs. Abstract : A novel dedicated transceiver 16‐element antisymmetric dipole antenna array (8Tx/16Rx) combining L‐shaped and straight dipoles was designed and tested to improve parallel transmit and receive performance for cardiac MRI in pigs at 7 T. Parallel imaging with an acceleration factor up to R = 6 was possible while maintaining a mean g factor of 1.55 within the pig heart. CINE images acquired in vivo in two pigs demonstrated SNR and parallel imaging capabilities comparable to those of a reference 8Tx/16Rx loop array.